Prioritizing topics in guideline development: results of a two‐phase online survey of dermatologist members of the EADV. (13th November 2018) - Nast, A.; Gaskins, M.; Eisert, L.; Werner, R. N.; Borradori, L.; Marinovic, B.; Paul, C.; Dressler, C.
Abstract: Background: Most clinical guidelines in dermatology are encyclopaedic, covering a disease and its aetiology, diagnosis, treatment and prevention in their entirety. The usability and uptake of guideline recommendations might be improved by guidelines that are more concise and address specific questions ranked by users according to their perceived importance. Objective: To survey the largest association of dermatologists in Europe, identify which questions in their everyday practice they felt would benefit from short, evidence‐based guidance and rank these systematically. Methods: A two‐phase online survey using a structured ranking approach and the members directory of the European Academy of Dermatology and Venereology (EADV). Results: The first survey yielded 265 suggestions, indicating a response rate of 3.7%. We grouped all responses according to themes and subsequently combined these into a list of 35 broader topics. These were presented to all members of the EADV in the second survey (response rate: 9.7%), which yielded a list of the top 10 topics participants felt were most in need of guidance. The first three were 'Systemic drug treatment in dermatology during pregnancy and for women wishing to have children in the near future', 'alopecia areata' and 'interpretation of laboratory results in connective tissue diseases'. Conclusion: Our two‐phase survey of EADV members and a structured ranking process were practical to implement and yielded a list of the top 10 topics in dermatology and venereology for guideline development. Guideline dissemination needs to be improved, and practical, more concise guidelines may facilitate efforts to do so.